POTRET SPIRITUAL PENGALAMAN KEAGAMAAN MANUSIA: (Tinjauan Narasi Musafir Plaform Youtube “Sinau Hurip”) - Achmad Sofiyul Mubarok (LPPM STAI Nida El-Adabi, 2024)
The spiritual aspect and spirituality will always exist in every human being. This indicates that in human life it will continue to coexist with religion. Religious actors will experience religion. Like a traveler who performs worship not as usual, apart from prayer, he walks along the road as a servant to Allah SWT. This paper aims to examine the spiritual side and religious experiences of travelers. This research is a etnographic research, to review the traveler's narrative on the YouTube platform “sinau hurip”. Using Joachim Wach's theory and concept of religious experience, the results of this study show that travelers carry out religious laws based on several forms of expression of religious experience: First, in the form of intellectual/ thought, he is a person who is aware of his behavior (not ODGJ) and always remembers the obligation to worship. Second, in the form of action, he applies worship and holds the principles of being a traveler such as being prohibited from asking, stealing and hoping that someone will have mercy. Third, in the form of fellowship he belongs to a small group. Which is not written in quantity. However, he feels a greater sense of solidarity and a strong inner bond.